TELEHEALTH-BASED PSYCHOSOCIAL SUPPORT FOR WOMEN WITH BREAST CANCER: A NARRATIVE REVIEW - Nuraeni, Aan; Trisyani, Yanny; Anna, Anastasia; Priambodo, Ayu Prawesti; Sugiharto, Firman (Journal of Maternity Care and Reproductive Health, 2026)
Breast cancer is one of the most common malignancies among women worldwide and is associated with multidimensional burdens throughout the disease trajectory, including diagnosis, treatment, and survivorship. Beyond physical symptoms, women with breast cancer frequently experience psychosocial problems such as anxiety, depression, emotional distress, and impaired quality of life, which may persist even after active treatment and influence treatment adherence and long-term outcomes. Conventional psychosocial support is typically delivered through face-to-face interactions; however, access to such services is often limited by geographical, temporal, and resource-related constraints. Telehealth has emerged as a promising approach to support psychosocial care by utilizing information and communication technologies to deliver health services remotely. In the context of breast cancer, telehealth encompasses various modalities, including mobile health applications, web-based platforms, teleconsultations, text messaging, and remote monitoring systems. Recent developments also indicate a growing integration of artificial intelligence, such as chatbots and conversational agents, to enhance information delivery and emotional support. This narrative review aims to critically discuss the role of telehealth in providing psychosocial support for women with breast cancer. Relevant literature was identified through searches of major scientific databases and analyzed descriptively to explore psychosocial challenges, telehealth concepts, and potential benefits for mental health and patient engagement. The findings suggest that telehealth may contribute to improved access to psychosocial support, enhanced coping, and increased patient involvement in care, although evidence remains heterogeneous across intervention types and outcomes. Telehealth should be considered a complementary approach within holistic breast cancer care, with careful attention to individual needs, digital literacy, and implementation context.